Forecasting Petroleum Fuel Price in Malaysia by ARIMA Model - Sokkalingam, R. (Springer Science and Business Media B.V., 2021)
Over the years the retail price of petroleum fuel in Malaysia, Ron95, Ron97 and Diesel have been controlled by the governments using the Automatic Price Mechanism (APM) which made the price of fuel in Malaysia relatively stable up until 2004. Beyond the year 2004, the price of petroleum fuel has been volatile even with the APM still being implemented. Even after changing the Policy to Managed float system in 2016 fuel prices have still not been stable. Reasons that have been attributed to the volatilities are the international crude oil price and foreign exchange volatilities and reduction of subsidies to improve government fiscal space. Predicting fuel Prices has become difficult. In this paper we apply the Time Series method Autoregressive Integrated Moving Average (ARIMA) to model and forecast fuel price. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.